The impact of gender differences on the conflict management styles of managers in Bangladesh : an analysis - Sogra, Khair Jahan (Cambridge Scholars Publishing, 2014)
Conflict is a common occurrence in organisations, and with the advent of women in the managerial realm researchers have become interested in the question of whether women and men vary significantly in their choices of conflict management styles. This interest has encouraged many researchers to investigate the issue of gender differences and conflict management mixed-method research underlying causes; and in Bangladesh, there none. To fill this gap, a cross sectional field study was undertaken Dhaka, Bangladesh incorporating both quantitative and qualitative analyses. -- The aim of this thesis is to explore the influence of contextual factors, including the present socio-cultural and economic changes taking place in the country, on the choice of conflict management styles of managers in Bangladesh and the factors that might create gender differences in managerial style. Earlier researchers have studied the issue using biological sex, age, education, managerial hierarchy, and gender role orientation as predictors and yet not organisational environment. The present research differs from all previous studies by linking managers' choice to organisational environment, which refers to day-to-day practices in organisations permeated with individuals' socio-cultural expectations and general economic conditions of the country. -- The findings of the present study suggest that exhibiting socially expected roles and using conflict management modes do not occur in vacuums. Both of them influenced by socio-cultural expectations governed by a rigid patriarchal system, organisational processes, and the magnitude of individuals' unsatisfied needs. All these factors in various combination affect the managerial styles of managers, and female managers emulate the well-accepted male managerial styles as a survival mechanism in the workplace. This results in no apparent gender differences in the preference of conflict management styles among managers, though the reasons for choosing a particular style may vary between females and males. -- An in-depth qualitative analysis reveals that socially prescribed gender congruent roles are not fixed but fluid. Men and women both are adopting either task oriented (dominating) or relationship oriented (obliging) managerial styles in response to situations and organisational demands. This trend is more pronounced in the NGO sector pursuing welfare goals and in other sectors, at senior managerial levels especially among senior level female managers. The latter group is more at liberty to use relationship orientation since they already have established themselves 'as effective as men'. However, it is encouraging that there is an undercurrent of change in organisations in terms of managerial styles and steadily, organisations are recognising that a synthesis of feminine and masculine styles can achieve better results in organisations.